COMPUTER SCIENCE STUDENTS’ ATTITUDES TOWARDS ENGLISH LANGUAGE LEARNING - iswahyuni iswahyuni (Fakultas Ilmu Budaya, Universitas Brawijaya, 2018)
This study is intended to know the attitudes of Computer Science students in Universitas Brawijaya towards English Language Learning in term of cognitive, affective, and conative aspects. It is a quantitative study and survey was used to collect the data. There were 100 students out of 954 students of Computer Science students of Universitas Brawijaya who became the sample of the study. The instrument used was Gardner’s Attitude and Motivational Test Battery (AMTB) questionnaire consisting of 46 items with four Likert Scale. The findings show that the samples gave positive attitude toward English learning in terms of all aspect. It means that all of them really interested in their English class.